Green credit policy, corporate social responsibility and green innovation - Zhang, Zhi (Journal of Business Economics and Management, 2024)
Human activities have an increasingly serious impact on our natural surroundings. Hence, cutting-edge sustainable technologies are essential for both governmental agencies and the corporate sector as a pivotal means to safeguard the environment. This study aims to shed light on the function that corporate social responsibility (CSR) plays in enterprises by examining the relationship between green credit policy (GCP) and green innovation (GI). This research examines a total of 5,819 panels of Chinese listed businesses’ data spanning from 2009 to 2021. The differences-in-differences (DID) model was used to assess hypotheses. The empirical results suggest that GCP has facilitated the adoption of GI by firms. GI in heavily polluting firms was elevated by 15% relative to the control group. The presence of CSR serves as a mediating and moderating factor in the relationship between GCP and the implementation of GI initiatives within firms. Lastly, based on the empirical results, relevant suggestions for optimizing GCP are proposed to achieve better environmental protection results.